EVALUASI DAYA HASIL 8 GENOTIPE CABAI (Capsicum annuum L.) DI LAHAN GAMBUT - Dio Inardo; Wardati '; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objectives of this research to evaluate potential yield of 8 genotypes of chili which grown on peatland. This research conducted for 6 months from January to June 2013 in peatland experimental station, Faculty of Agriculture, University of Riau, Rimbo Panjang, Kampar. Randomized block design which is consist of 8 treatment and 3 replications was used in this experiment. Variable those observed were flowering date, plant height, stem diameter, dichotomus height, canopy width, harvesting date, weight per fruit, fruit length, fruit diameter and weight of fruit per plant. Data obtained from the observations were statistically analyzed by using analysis of variance, and mean separation by Duncan's New Multiple Range Test (DNMRT) at the level 5%. The results showed that genotypes of chili had good adaptability and yield. Genotype IPB C19 has a higher fruit weight per plant is higher than Gada. Genotype IPB C111 did not significantly different compare to TM999 on fruit weight per plant.   Keyword : yield evaluation, chili, peatland